Depression: a common comorbidity in women with rheumatoid arthritis—results from an Austrian cross-sectional study - Judith Sautner; Rudolf Puchner; Alois Alkin; Herwig Pieringer (BMJ Open)
Objectives Previous research showed that depression is common in rheumatoid arthritis (RA). However, the prevalence very much depends on different assessment tools and sociocultural differences, respectively. The main study aim and research question was to investigate the proportion of depressive symptoms in Austrian female patients with RA.Setting A nationwide multicentre study with seven secondary care centres all over Austria (hospital-based rheumatological outpatient clinics and private practices).Participants 319 patients with RA and 306 healthy controls (HCO), all female Caucasians, were asked to complete a Beck’s Depression Inventory–Fast Screen (BDI-FS). Patients and HCO were ≥18 years. Patients had to fulfil the 2010 classification criteria for RA. In addition, disease activity, disability, medication, drinking of alcoholic beverages, smoking and occupational status were evaluated.Primary and secondary outcome measures A BDI-FS cut-off value of ≥4, per definition, indicates the presence of a depressive symptomatology.Results The return rate of questionnaires was high: 235/319 (73.7%) in patients with RA and 180/306 (58.8%), ending up with 392 complete questionnaires from 223 patients with RA (69.9%) and 169 HCO (55.2%). The BDI-FS was significantly higher in patients with RA (median BDI-FS 2 (IQR 0–4) vs median 1 (IQR 0–2) in HCO, p<0.001). BDI-FS scores from ≥4, which by definition indicate depression, were found in 29.6% of patients with RA and 12.4% of HCO (p<0.001). Depressive symptoms were strongly associated with disease activity (Clinical Disease Activity Index, p<0.001) and disability (Health Assessment Questionnaire, p<0.005). No association of depressive symptoms with age, alcohol consumption, smoking, occupational status or use of medication was found.Conclusions One-third of female patients with RA showed depressive symptoms. Depression was significantly higher in female patients with RA than in female HCO and was strongly associated with disease activity and disability. It would be of interest to address the same question in male participants.